Outcomes Associated With Planned Place of Birth Among Women With Low-Risk Pregnancies. Issue 4 (April 2016) - Hutton, Eileen K.; Cappelletti, Adriana; Reitsma, Angela H.; Simioni, Julia; Horne, Jordyn; McGregor, Caroline; Ahmed, Rashid J.
Abstract : Obstet Gynecol Surv 2016;71(4):205–206 In the past century, Western culture has come to view hospital birth as safer than home birth.